(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2017)
Utilizing ergonomics during medical equipment development and system design increases patient safety and efficiency in the working environment. The purpose of this report is to review the current literature on the use of ergonomics during medical equipment development and system design. To support the efficient use of existing ergonomics, there are techniques and methods that form an application for usage in the development process. The literature review will illustrate heuristics, design methods and design guidelines that ergonomists utilize during medical equipment development and system design.